Insuficiencia respiratoria aguda en paciente femenino de 68 años con antecedentes de diabetes. - Hidalgo Aspiazu, Yadira Johanna (2020)
Respiratory failure is a complication characterized by the inability of the body to maintain arterial levels of oxygen and carbon dioxide. The present clinical case is a 68-year-old patient, upon admission 5-day clinical picture characterized by moderate intensity interscapular pain, diaphoresis and minimal effort dyspnea, oriented in 3 spheres, hypertensive, tachycardic, tachypneic Bilateral afebrile roncus, as the main symptoms, in addition to having a hypertensive history, long-standing diabetic and heart disease. We must bear in mind that respiratory failure is not a pathology, but a complication resulting from other types of pathologies that may be affected by the organism. Laboratory tests such as chest x-rays and gasometry were the main diagnostic measures to verify or rule out other type of involvement at the pulmonary level, as for gasometry it presented abnormal values of arterial gases. The patient is discharged in a short time, chicho responded favorably to the treatment.